Argumentacja geopolityczna w prasie polskiej 1945-1948 jako element realizacji polskiej myśli zachodniej = Geopolitical reasoning in the Polish press of 1945-1948 as an element of implementing Poland's western ideas - Domke, Radosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A significant amount of press articles stresses Poland's geopolitical rights to the western territories. On the one hand, it is being emphasized that the border is more beneficial for us now than during the pre-WWII period and on the other hand, the society is being convinced that the fact that Germany's eastern border is placed on Oder and the Lusatian Neisse has fundamental meaning for the safety of the whole of Europe. A lot of place related to geopolitics and security is being dedicated to Poland's gaining of over 500-kilometer-long Baltic sea-coast.
Keywords: Ziemie Zachodnie i Północne; prasa polska; Polska - historia - do 1989 r.